Equivalence of Similes in the Arabic Translation of the Symphony of the Dead Novel Based on the Pierini Model (2007) - Habib Keshavarz (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2020)
Simile is one of the most important rhetorical techniques that in addition to literary poetry and prose is also widely used in non-literary texts. Therefore, in the translation process, the issue of metaphor translation is also one of the most important challenges for translators. The greatest difficulty in translating a metaphor is due to the cultural differences between the target language and the source language. In this respect, determining the correct method in translating the phrases in which the analogy is used can reduce the difficulty of this task, and this depends on the skill and approach of the translator. In this article, we will use a qualitative method to examine the methods used in translating the similes in the Arabic translation of the novel "Symphony of the Dead" performed by Ahmad Musa, and for this purpose, we will use the model of Pierini (2007). Pierini generally suggests six methods for translating metaphors in a text. The results of this study show that these methods are suitable and applicable for the study of metaphorical translation. In translating the novel, Ahmad Musa has used the literal translation method the most. Excessive use of the literal translation method indicates the closeness of the culture in the source and target language and the translator's tendency to alienate the target text. The Pyrenean model also needs to be completed, and strategies such as adding metaphorical devices need to be added.